Neonatal perforated appendicitis, a rare presentation to a localized form of necrotizing enterocolitis - Reham Alsereihi; Lujain Alzahrani; Waad Haroun (Elsevier, 2022)
Neonatal perforated appendicitis is a rare diagnosis that is usually made intraoperatively. Despite the existence of multiple etiologic theories, rising evidence points to a subset of Neonatal perforated appendicitis (NPA) cases as becoming a localized form of necrotizing enterocolitis (NEC). We present a case report of a 5 day old girl with intraoperative diagnosis of perforated appendicitis.